Diabetes mellitus augments the complications of patients with COVID-19: a review - Pramanik, Parthiba; Pramanik, Purushottam (International Journal of Research in Medical Sciences, 2020)
Corona virus disease 2019 (COVID-19) is current pandemic infection caused by RNA virus named severe acute respiratory syndrome coronavirus-2 (SARS Cov-2). The lungs are the organs most affected by COVID-19 and people were died due to severe acute respiratory s syndrome, pneumonia and multi-organs failure. Fatality rate was more, those who suffer in chronic diseases including diabetes mellitus (DM). As COVID-19 pandemic is accelerating , it is important to understand the molecular mechanism through which DM increases the severity related to COVID-19 to able to design more appropriate therapy. The aims of this study was to identify mechanisms through re-analysis of publicly available data by which DM increases susceptibility for COVID-19 infection and/or increase complication for SARS-Cov-2 infection. SARS Cov-2 accesses host cells via membrane bound enzyme, angiotensin converting enzyme-2 (ACE2). This leads to imbalance of vasoprotective and vasodeletorious arms of renin angiotensin system (RAS) with over activity of vasodeletorious arms. Such imbalance of RAS induces alveolar damage, flooding the alveoli and difficulty in breathing. DM augmented the chance of pulmonary infection by impairment of innate immunity and down regulation of ACE2. Hence, diabetic patients of COVID-19 die from multi-organ failure, shock, heart failure, arrhythmias and renal failure along with severe acute respiratory syndrome. Thus it is concluded that DM augments the complications from COVID-19 by enhancing development of RAS imbalance. From view point of public health it is suggested to keep the lung healthy, maintain blood glucose level properly, and intake foods rich in antioxidant and anti-inflammatory agents to prevent and ameliorate the acute effect of COVID-19 in diabetic patients.